Pengembangan Agrowisata dan Pemberdayaan Petani Kopi di Ciwidey, Jawa Barat Melalui Pendampingan oleh Akademisi - Ramonita, Latifa; Yunus, Ulani; Husada, Safaruddin (Politeknik Negeri Jember, 2025)
Ciwidey as a coffee-producing highland in West Java that has beautiful panorama offers opportunities for agro-tourism development. Unfortunately, this potential has not yet been developed optimally. This research seeks to explore collaboration between academics and stakeholders in the development of sustainable agro-tourism in the Ciwidey area. Through on-site training related to agro-tourism and in-depth interviews with the community, this study seeks to reveal the importance of sharing knowledge and resources, as well as joint learning to encourage innovation and involvement of local communities. Through efforts to bridge the gap between academia and industry, it is hoped that this collaborative model can help develop the socio-economic prospects of the Ciwidey community, contributing to the efforts to preserving Sundanese culture and its environment. Descriptive qualitative methods by applying Rogers' Diffusion of Innovation theory is applied for this research methodology, involving 11 informants. The results of this activity help provide a roadmap for stakeholders who want to develop agro-tourism in Ciwidey, encouraging sustainable empowerment and partnerships between academia and industry.